Three bags full - Swann, Leonie, 1975- (Swann, Leonie, 1975- Sheep detective stories, 2025)
"Something is not right with George the shepherd. His sheep have gathered around him on a hill outside the cozy Irish village of Glennkill to assess the situation. George has cared for the sheep, reading them books every night, and now he lies pinned to the ground with a spade. His flock, far savvier about the workings of the human mind than your average sheep, set out to find George's killer, led by Miss Maple, the smartest sheep in Glennkill (and possibly the world). Her team of investigators includes Othello, the "bad-boy" of the group; Mopple the Whale, a merino who eats a lot and remembers everything; and Zora, a thoughtful, if gloomy, ewe--just to name a few. Together, the sheep engage in nightlong discussions about the crime, and their speculations vary wildly. Determined to get to the bottom of the mystery, they embark on furtive missions into the village, where they encounter some likely two-legged suspects. There's Ham, the terrifying butcher; Rebecca, the secretive village newcomer; Gabriel, the shady shepherd of a strange flock; and Father Will, a sinister priest. With wit and heart, this clever international bestseller is a mystery to chew on--and savor. This twentieth-anniversary deluxe paperback features a Foreword by A. J. Finn, discussion questions, and more"--